Knowledge management in small and medium enterprises: Literature review and research agenda - Alejandro Valencia-Arias; Orfa Nidia Pati\~no-Toro; Manuel Humberto Vásquez Coronado; Olga-Velez Bernal; Elizabeth Zea Marquina (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
Knowledge management is pivotal in analyzing organizational innovation, as it influences the capacity to achieve objectives and engage in corporate decision-making. Nevertheless, its application encounters constraints within small and medium-sized enterprises (SMEs) due to resource and knowledge barriers. Hence, scholarly literature must remain current to offer solutions. Consequently, the study aims to explore trends in knowledge management research within SMEs. To achieve this, a bibliometric analysis is conducted employing the Scopus database, adhering to PRISMA statement guidelines. Excel and VOSviewer software are employed for data analysis. This study's perspective delves into the thematic evolution over time, encompassing both areas of sustained development and emerging trends. The findings underscore significant trends that emphasize the pivotal importance of innovation as a driver of organizational performance and advancement. This emphasis is underpinned by the adoption of open innovation approaches, fostering knowledge transfer and exchange to nurture internal learning. Notably, the study highlights the concepts of knowledge absorption capacity and dynamic capability development as fundamental cornerstones for propelling intellectual capital growth and business model adaptation.
Keywords: O32; L25; M15; 330; Innovation; Open Innovation; Sustainable Development; Bibliometric Analysis; Knowledge Management; Small And Medium Enterprises (SMEs); Prisma; Organizational Learning